2017
DOI: 10.1097/ncc.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Factor Analysis of the Strength of the Cultural Affiliation Scale

Abstract: Background Within the United States there are individuals who retain traditions and beliefs of cultural groups that vary from the general majority population. Both health care providers and researchers have reported that many individuals who live in but are less affiliated with the dominant culture tend to have less positive health outcomes. Objective The purpose of this study was to use factor analysis to assess the psychometric properties of Mood's 18-item Strength of Cultural Affiliation Scale (SCAS). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The global C-MTBQ scores were skewed and varied from 2 to 60. None of participants had a global C-MTBQ score of 0, and no treatment burden(0), low treatment burden(< 10), medium treatment burden (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and high treatment burden (≥22) accounted for 0, 14.7, 39.7 and 45.5%, respectively. The median C-MTBQ total score was 20.8 (interquartile range 12.5-29.2).…”
Section: The Descriptive Statistics Of the C-mtbqmentioning
confidence: 99%
See 1 more Smart Citation
“…The global C-MTBQ scores were skewed and varied from 2 to 60. None of participants had a global C-MTBQ score of 0, and no treatment burden(0), low treatment burden(< 10), medium treatment burden (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and high treatment burden (≥22) accounted for 0, 14.7, 39.7 and 45.5%, respectively. The median C-MTBQ total score was 20.8 (interquartile range 12.5-29.2).…”
Section: The Descriptive Statistics Of the C-mtbqmentioning
confidence: 99%
“…The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy(0.776) and the Bartlett test of sphericity (p < 0.001) showed that factor analysis of the data was appropriate [21,22]. The scree plot is shown in Fig.…”
Section: Factor Analysismentioning
confidence: 99%